2012
DOI: 10.1155/2012/943653
|View full text |Cite
|
Sign up to set email alerts
|

Highlights for Management of a Child with a Urinary Tract Infection

Abstract: Urinary tract infections remain the most common bacterial infection in childhood. Escherichia coli is responsible for over 80% of Pediatric UTIs. Other common gram negative organisms include Kleibsiella, Proteus, Enterobacter and occasionally Pseudomonas. Signs and symptoms vary greatly by age of the patient becoming more specific as the child grows older. Even in the absence of specific signs a UTI should be included in the differential diagnosis of high grade fever. In younger children, presence of upper res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
16

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 51 publications
2
41
0
16
Order By: Relevance
“…1,2,4 Other common gram negative organisms include Klebsiella, Proteus, Enterobacter, and occasionally Pseudomonas. Fungal infections are much less common and are usually to those who are immunecompromised or diabetic, are on long-term antibiotics, or have long-term indwelling catheter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,4 Other common gram negative organisms include Klebsiella, Proteus, Enterobacter, and occasionally Pseudomonas. Fungal infections are much less common and are usually to those who are immunecompromised or diabetic, are on long-term antibiotics, or have long-term indwelling catheter.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Antibiotic resistance and multi-drug resistant infection, driven by antibiotic use, remain a major public health and professional concern.…”
Section: Introductionmentioning
confidence: 99%
“…Proteus species was isolated in 43 (10.1%) samples and of the Proteus species 38 (88.4%) were identified in males. Previous studies have shown that Proteus species causes more UTIs in males [14][15][16] . In one study from Turkey Proteus species were isolated only in male patients 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of UTI is greater in girls as compared to boys, which may be either due to anatomical structure or physiologic mechanisms (6,7). In boys, UTIs are much more common in uncircumcised boys especially during the first year of their life (8). Enteric Gram-negative bacteria are the most common cause of urinary tract infections, with Escherichia coli being the predominant pathogen (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Gram-positive bacteria, including Staphylococcus spp and Streptococcus spp (e.g. S. saprophyticus, Enterococci) have also been reported as pathogens in children with UTI (8)(9)(10). Delay in diagnosis and appropriate treatment is the cause of complication in the upper genitourinary system (5).…”
Section: Introductionmentioning
confidence: 99%